The conceptualization of Civic Education in Costa Rica: contributions from professionals associated with the discipline. - Alfaro Valverde, Alicia (2013)
This article is the product of a research Project entitled “Conceptualization and perception about Civic Education among teachers of Social Studies and their students in the 10th and 11th grades at the secondary school level.” Its main purpose is to share a number of reflections regarding the conceptualization of Civic Education in Costa Rica, which derive from the contributions of a diverse group of professionals involved in this field of study. Additionally, the paper takes into consideration the emphasis and characteristics attributed to this subject matter as a cross curricular theme that brings together a diversity of processes that take place within and outside the classroom.